Destination Dixie : Tourism and Southern History - Cox, Karen L., 1962- (University Press of Florida, 2012)
Once upon a time, it was impossible to drive through the South without coming across signs to "See Rock City" or similar tourist attractions. From battlegrounds to birthplaces, and sites in between, heritage tourism has always been part of how the South attracts visitors - and defines itself - yet such sites are often understudied in the scholarly literature. As the contributors to this volume make clear, the narrative of southern history told at these sites is often complicated by race, influenced by local politics, and shaped by competing memories.